2008
DOI: 10.1111/j.1365-2656.2008.01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural female mating rate maximizes hatchling size in a marine invertebrate

Abstract: Summary 1.Males and females often differ in their optimal mating rates, resulting potentially in conflicts over remating. In species with separate sexes, females typically have a lower optimal mating rate than males, and can regulate contacts with males accordingly. The realized mating rate may therefore be closer to the female's optimum. In simultaneous hermaphrodites, however, it has been suggested that the intraindividual optimization between 'male' and 'female' interests generates more 'male'-driven mating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…A randomly sampled individual in the population will normally gain more from mating next as a male, because it likely has mated as a female already. The empirically observed Bateman gradients thus probably mean that these snails show a male sex-role preference (Anthes et al 2010;Pélissié et al 2012), and two studies on sea slugs, in which only the female function was examined, even suggested costs for high female mating rates (Sprenger et al 2008;Lange et al 2012).…”
Section: Premating Conflicts: Sex-role Preferencesmentioning
confidence: 99%
“…A randomly sampled individual in the population will normally gain more from mating next as a male, because it likely has mated as a female already. The empirically observed Bateman gradients thus probably mean that these snails show a male sex-role preference (Anthes et al 2010;Pélissié et al 2012), and two studies on sea slugs, in which only the female function was examined, even suggested costs for high female mating rates (Sprenger et al 2008;Lange et al 2012).…”
Section: Premating Conflicts: Sex-role Preferencesmentioning
confidence: 99%
“…Choosing to invest in sexual conflict arms races over fecundity should be widespread among simultaneous hermaphrodites, according to recent theoretical work [36,37]. There is also empirical evidence suggesting that elevated mating rates may have opposite fitness effects via male and female sex functions [38,39]. (iv) Mediation of parasite-associated effects.…”
Section: Intra-locus Sexual Conflict In Hermaphroditesmentioning
confidence: 99%
“…Early larval survival (prop) 0.410 1.08 9 10 -2 (12.7) 2.85 9 10 -2 (33.4) 4.61 9 10 -2 (53.9) V A , additive genetic variance; V M?D , maternal and dominance variance; V E , environmental variance (Sprenger et al 2008a;Sprenger et al 2008b) is independent of a male's genetic quality and is not affected by the genes or the environment (e.g., accessory substances) provided by males. Recent suggestive evidence for the dependence of maternal allocation on the genetic compatibility (i.e., genetic quality) between parental genotypes derives from the live bearing pseudoscorpion Cordylochernes scorpioides.…”
Section: Parental Effects On Offspring Size and Early Life History Trmentioning
confidence: 99%
“…Recent experimental work showed that polyandrous mothers (mated to four different partners) produce larger but not fewer eggs and larvae than repeatedly mated (four times to the same partner) and singly mated females (Sprenger et al 2008a). Moreover, per-offspring investment was maximized at an intermediate mating rate matching that accomplished in the field (Sprenger et al 2008b). Changes in mean offspring size did not affect the variance in offspring size between females (Sprenger et al 2008a;Sprenger et al 2008b), indicating non-selective sperm usage by females (García-González and Simmons 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation